2016
DOI: 10.1159/000446611
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Patients with Deep Brain Stimulation of the Centromedian Thalamic Nucleus for Refractory Epilepsy and Location of the Active Contacts

Abstract: Objectives: To investigate the clinical outcome of patients treated with chronic deep brain stimulation (DBS) of the centromedian nucleus (CM) for refractory epilepsy and to determine the location of active contacts. Methods: The outcome of CM stimulation was evaluated as percent seizure reduction compared to the baseline 3 months. To establish the location of active contacts, 27 leads were studied in 14 patients with refractory epilepsy. An analysis was conducted to reveal whether any coordinates of the cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 30 publications
5
93
0
Order By: Relevance
“…Velasco et al investigated the effect of stimulating the centromedian nucleus for treating generalized seizures in 13 patients with Lennox‐Gastaut syndrome and found that the overall seizure reduction was 80% at 18 months. Similarly, Son et al found that centromedian thalamic nuclei stimulation effectively reduced seizures in 11 of 14 patients, including 100% of those with Lennox‐Gastaut syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Velasco et al investigated the effect of stimulating the centromedian nucleus for treating generalized seizures in 13 patients with Lennox‐Gastaut syndrome and found that the overall seizure reduction was 80% at 18 months. Similarly, Son et al found that centromedian thalamic nuclei stimulation effectively reduced seizures in 11 of 14 patients, including 100% of those with Lennox‐Gastaut syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not elicited in the most proximal electrode contact landing outside the thalamic tissue, within the lateral ventricle, as verified by postoperative MRI in 2 patients in whom the electrodes did not extend more deeply than the calculated border of the anterior nucleus [6]. Although elicitation of DR was an essential observation in the SANTE trial [2], DR and an intraoperative EEG study, such as single pulse electrical stimulation through the electrode contacts, are regarded as an essential step to verify the final electrode position in some centers [9,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Many structures have been the target of stimulation in human trials to improve seizure control ( Fig. 1 and Table 1), including the ANT, 2,20,39,57,66 the centromedian nucleus of the thalamus (CMT), 21,52,60,64,67 the cerebellum, 4,65,69,75 the hippocampus, 5,7,14,15,30,68,73 and the subthalamic nucleus (STN). 10,26,36,71 Common DBS Targets…”
Section: Mechanism Of Action and Preclinical Datamentioning
confidence: 99%